Effects of virtual reality-based exercise intervention in young people with attention-deficit/ hyperactivity disorder: a systematic review - Jia-Ling Sun; Xiao-Jun Chaw; Shane Fresnoza; Hsiao-I. Kuo (Journal of NeuroEngineering and Rehabilitation, 2025)
Abstract Background Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder among the young population in the world. Young people with ADHD are often affected in their performance of attention, behavior, and executive functions (EFs), leading to a limited quality of life. Recently, Virtual reality (VR)-based exercise has been used as an intervention for young people with ADHD. Therefore, this review aims to evaluate the effectiveness of VR-based exercise in improving EFs and reducing ADHD symptoms in young people. Method This review aims to systematically review the effects of VR-based exercise on the overall EFs and their subdomains, as well as ADHD symptoms in young people with ADHD. This review was registered in the International Prospective Register of Systematic Reviews (PROSPERO CRD42024604205) and was funded by the National Science and Technology Council, R.O.C., with the project number 112-2314-B002-119-MY3. Studies were identified in five databases (Cochrane Library, Web of Science, PubMed, SCOPUS, and Embase) from September 2010 through September 2024. Studies that applied VR-based exercise intervention on young participants with ADHD were included in this systematic review. A total of 6 studies met the inclusion criteria and were considered high quality according to standardized assessment lists. Results Based on the 6 included studies and a total of 192 participants, the results showed that VR-based exercise with moderate to vigorous intensity provides positive effects on multiple subdomains of EFs (inhibitory control, attention, working memory, switching, and planning) and clinical symptoms in young people with ADHD. Furthermore, fully immersive and semi-immersive VR-based exercise interventions yielded similar results. Conclusion VR-based exercise effectively improves EFs and is feasible for young people with ADHD, with benefits observed across ages and with sessions over 30 min. However, more evidence is essential for VR-based exercise intervention, which may compare the effects to other intervention types. Additionally, studies with rigorous experimental design are warranted.